Developing a model of partnership management between the vocational high school and the employment domain in the curriculum of industrial working practice - Harbiyah Gani; Husaini Usman (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
The study was to develop a model of partnership management between the vocational high school (VHS) and the employment domain in the curriculum of industrial working practice under the activities of planning, implementation, monitoring, and evaluation in the vocational high schools of Banda Aceh. The study used the research and development method design with several phases that had been developed by Borg & Gall. The data type in the study was qualitative and quantitative. For the qualitative data analysis, the researcher used the interactive analysis that had been developed by Milles & Huberman. On the other hand, for the quantitative data analysis the researcher used a Likert-scale measure. The research subjects were vocational education practitioners and experts. The data gathering was conducted by means of documentation, observation, interview, and Delphi techniques; all of the methods were implemented until the researcher found the conceptual model. Then, the researcher involved the experts in the model testing by using the Delphi technique resulting in a hypothetical model from the conceptual to be used as the basis for developing the final model. Eventually, the researcher drew the following conclusion: (1) The partnership between the VHS and the employment domain had been pursued by all of the vocational high schools in the City of Banda Aceh but there had not been any clear and integrated model of partnership management; and (2) the researcher generated a model development of partnership management between the VHS and the employment domain in the curriculum of industrial working practice clearly, practically, and effectively.